Hubungan Pelaksanaan Promosi Kesehatan dengan Kepatuhan Ibu Hamil dalam Melengkapi Imunisasi TT PMB Ellna Palembang 2025 - Dwi Agustin Prima Lestari, Leonita (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Maternal and neonatal tetanus remains a preventable health problem through the administration of Tetanus Toxoid (TT) immunization to pregnant women. Although immunization programs are available, the completeness of TT immunization in various regions remains low and is influenced by the effectiveness of health promotion. This study aims to determine the relationship between health promotion and the completeness of TT immunization among pregnant women at PMB Elna Palembang. This research used a quantitative design with a cross-sectional approach. The sample consisted of pregnant women who met the inclusion criteria, selected using purposive sampling. Data were collected using a questionnaire assessing the quality of health promotion and the completeness of TT immunization based on the Maternal and Child Health (MCH) book. Data analysis was performed using the Chi-square test to determine the relationship between the two variables. The results showed that most respondents received health promotion in the good category, and the majority of pregnant women had complete TT immunization status. There was a significant relationship between health promotion and TT immunization completeness (p < 0.05). Thus, effective health promotion plays an important role in improving the compliance of pregnant women in completing TT immunization. Health workers are expected to enhance educational activities, counseling, and routine monitoring to support the achievement of optimal TT immunization coverage.